Co-Constructed Oppositional Stance and Facework in an Office Hour Interaction - Çiftçi, Hatime; Vásquez, Camilla (De Gruyter, 2020)
Stance plays a salient role in communicating interpersonal meaning through language use. Understanding stance as co-constructed within dialogic interaction uncovers subtleties of how interlocutors use language to express their subjectivities and thus, negotiate their interpersonal relationship. The notion of face and facework, or relational work (Locher 2004), is therefore relevant to the understanding of stance in interaction. Drawing on Du Bois’ (2007) stance triangle, our study analyzes oppositional stance in a single, extended interaction and shows how two interlocutors in an academic setting jointly construct oppositional stance, each by drawing on their own interpretations. Our analysis indicates that this co-constructed oppositional stance is enacted throughout three broader stages, which we call initiation, negotiation, and resolution. We also demonstrate that expressing oppositional stance is a complex process where interlocutors employ various discourse strategies to express pessimistic evaluation, shifting positionings, and (dis)alignment. Meanwhile, instances of oppositional stance become face-maintaining and face-challenging at different stages in which directness and indirectness are variably employed.
Keywords: Epistemic stance; Affective stance; Interactional sociolinguistics; Facework; Oppositional stance